REGIONAL OUTLINES SPATIAL COMPETITION - Boris T. Morgoev (Вестник Северо-Кавказского федерального университета)
The article deals with regional characteristics of spatial competition, a classification of spatial competition through the levels, type, subject, object, types, methods, types, forms, allowing you to more clearly otchertit subject-object structure of competition in the spatial aspect of the development of regional economic subsystems.